Design and Implementation of a SCADA-Controlled MTMPS as a Mechatronics Training Unit - (:unkn) unknown (WILEY-BLACKWELL, 2012)
Recently, economical aspects of education have become an important issue for everyone who is in the educational sector since they have to operate on restricted budgets. Therefore, the limited resources of educational institutions have necessitated the development of novel teaching materials. The aim of this study is to design and implement a low-cost compact Modular Production System controlled by a Supervisory Control and Data Acquisition (SCADA) system. This compact MPS has the following stations: identification, transport, processing, sorting, and storing. All these stations are placed on a common platform and connected to the same PLC system. Therefore, it is proposed that this system can be called as 7Multitask Modular Production System (MTMPS). The benefits of the realized MTMPS are threefold. This system resulted in savings both for occupied space and cost of equipment. Savings for occupied space is nearly 70% while it is about 80% for the cost of equipment. The duration of training are also reduced by 60% with the implementation of this MTMPS. This study also includes evaluation of training course conducted on the MTMPS and conventional MPS units. As a result of this training, which employs the MTMPS unit, the students were expected to enhance their various cognitive skills. (C) 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 20: 247-254, 2012; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.20391
Keywords: multitask modular production system (MTMPS); design and implementation; MPS; SCADA control; PLC; mechatronics training material; UNIVERSITY